A novel strategy to promote microalgal growth and lipid productivity by supplementation of lignin related phenolic elicitors - Zhu, Jiangyu; Tan, Xiaomiao; Saadiah Hafid, Halimatun; Wakisaka, Minato (Elsevier, 2023)
An environment-friendly and cost-effective approach to improving lipid productivity without sacrificing microalgal growth was established. Syringic acid (SA) and p-coumaric acid (p-CA) are two major lignin hydrolysates, widely distributed in the wastewater from downstream industries of lignin. In this study, their potential in regulating the growth and valuable metabolites biosynthesis of microalga Euglena gracilis was evaluated. The cell growth was increased by 1.63 and 1.93 times at the optimal dosage of 0.5 g·L-1 SA and 0.3 g·L-1p-CA, respectively. Cell morphology also varied under the two treatments, reflecting the changes in cellular physiological status. Moreover, increased chlorophyll a content was only observed under p-CA treatment, indicating the influences of these compounds on photosynthesis were different. Fourier-transform infrared spectroscopy analysis revealed the fluctuations in the macromolecular pools. The variation trend of carbohydrate content was different under the treatment of the p-CA and SA, demonstrating that different phenolic compounds will determine different biosynthetic pathways and the flow of carbon to metabolites in microalgal cells. However lipid biosynthesis was improved by both of the phenolic acids treatments, which would be favorable to the biofuel production since the cell biomass was not sacrificed for lipid accumulation.